Enhancing the saturable absorption and carrier dynamics of graphene with plasmonic nanowires (Phys. Status Solidi B 10/2015). Issue 10 (7th October 2015) - Wang, Hancong; Miao, Lili; Jiang, Yaqin; Lu, Shunbin; Li, Zhipeng; Li, Pan; Zhao, Chujun; Zhang, Han; Wen, Shuangchun
<x xml:space="preserve">Abstract</x> The advanced nonlinear optical properties of graphene make it a promising candidate for laser mode locker, Q‐switcher, optical limiter, etc. The saturable absorption (SA) and carrier dynamics of graphene could be tailored by hybridizing graphene with noble metal nanowires. The results of Hancong Wang and coworkers (pp. 2159–2166) demonstrate that fewlayered graphene/silver nanowire hybrid films show enhanced SA response and tunable carrier dynamics, which are not only important for understanding the coupling mechanism between graphene and plasmonic nanostructures, but also for developing graphene‐based plasmonic devices. More importantly, this work offers a new strategic approach to modulate the nonlinear optical properties of two‐dimensional materials and their heterostructures, through mixing with one‐dimensional metallic nanowires, which may boost the development and applications of two‐dimensional material based nonlinear optics.